Physicochemical, functional and structural properties of the major protein fractions extracted from Cordyceps militaris fruit body. (April 2021) - Yu, Xiao-Ying; Zou, Yuan; Zheng, Qian-Wang; Lu, Feng-Xian; Li, De-Huai; Guo, Li-Qiong; Lin, Jun-Fang
Graphical abstract: Highlight: Cordyceps militaris fruit body is rich in proteins content of 29.81%. The protein fractions of Cordyceps militaris fruit body have a well-balanced amino acids composition. The protein fractions of higher surface hydrophobicity had shown favorable functional properties. The alkali-extracted protein structures were more unfolding and open. Abstract: The physicochemical and functional as well as structural properties of major protein fractions (albumin, globulin, glutelin) sequentially extracted in water, salt, alkaline solution respectively from Cordyceps militaris Minfu20 fruit body were investigated. The glutelin (43.11%, w/w ) was the predominant protein component of C. militaris fruit body followed by albumin (36.47%) and globulin (17.94%). The three proteins extracted from different solvents showed different characteristics, which were related to the alternation of amino acid composition, surface hydrophobicity, and structural feature. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) showed that the albumin and globulin mainly consisted of polypeptides with size < 20 kDa. The glutelin showed serious staining on the lane which may have a relatively bigger molecular weight. Intrinsic fluorescence intensity (FI) suggested glutelin contained more unfolding conformations (highest FI) which were probably resulted in a better foaming capacity of 151% and emulsion formation with the smallest size oil droplets (10.410 µm). The protein fractions showed great nutritional quality since they satisfied all recommended essential amino acid allowances for adults of Food & Agriculture Organization (FAO)/World Health Organization (WHO). Therefore, Cordyceps militaris Minfu20 fruit body proteins have potential alternative renewable edible fungi (mushroom) protein and could be used effectively as a food ingredient to improve food nutrition and product diversification compared with plant proteins.